BK virus infection in allogeneic hematopoietic cell transplantation: An update on pathogenesis, immune responses, diagnosis and treatments. Issue 3 (September 2020) - Saade, Anastasia; Styczynski, Jan; Cesaro, Simone; ,
Highlights: In hematopoietic cell transplantation patients, BKPyV-related hemorrhagic cystitis (HC) results in significant morbidity. An interaction exists between BKPyV and the immune system in the clearance of the virus. The use of BKPyV viremia as a screening tool to predict the onset or severity of HC remains controversial. Cidofovir efficacy is debated, while intravesical therapies warrant further research pending immunotherapies. Abstract: In hematopoietic cell transplantation (HCT) patients, BK polyomavirus (BKPyV) infection results in significant morbidity mainly due to hemorrhagic cystitis (HC). Despite increased knowledge acquired over recent decades, no treatment has shown effectiveness in the management of organ damage in HCT allografts. This review summarizes the current knowledge on BKPyV, from the virus constitution to the pathophysiology and immune-related mechanisms. We next focus on BKPyV-induced HC in HCT to discuss the benefit of monitoring BKPyV viruria and viremia in the management of patients. At last, we review currently used therapeutics, along with future promising therapies to propose clinical and practical guidelines and further interesting research areas.